2020
DOI: 10.1111/jipb.12896
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing winter for spring flowering: A molecular epigenetic perspective on vernalization

Abstract: Many over-wintering plants, through vernalization, overcome a block to flowering and thus acquire competence to flower in the following spring after experiencing prolonged cold exposure or winter cold. The vernalization pathways in different angiosperm lineages appear to have convergently evolved to adapt to temperate climates. Molecular and epigenetic mechanisms for vernalization regulation have been well studied in the crucifer model plant Arabidopsis thaliana. Here, we review recent progresses on the vernal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 110 publications
(217 reference statements)
2
61
0
Order By: Relevance
“…Recently, in addition to the elucidation of the signal transduction mechanisms underlying abiotic stress responses, increased numbers of studies have shown important participation of epigenetic mechanisms in the response of plants to abiotic stresses (Sahu et al 2013; Kim et al 2015). A good example of epigenetic regulation in plant response to the environment is the extensive involvements of epigenetic marks in vernalization, a process where plants remember a prolonged low temperature exposure in the winter in order to flower in the spring (Zhao et al 2018; Luo and He 2020). The epigenetic mechanisms of cold‐dependent vernalization have been well documented and will not be discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in addition to the elucidation of the signal transduction mechanisms underlying abiotic stress responses, increased numbers of studies have shown important participation of epigenetic mechanisms in the response of plants to abiotic stresses (Sahu et al 2013; Kim et al 2015). A good example of epigenetic regulation in plant response to the environment is the extensive involvements of epigenetic marks in vernalization, a process where plants remember a prolonged low temperature exposure in the winter in order to flower in the spring (Zhao et al 2018; Luo and He 2020). The epigenetic mechanisms of cold‐dependent vernalization have been well documented and will not be discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic mechanisms participate in the regulation of stress‐responsive genes at the transcriptional and posttranscriptional levels by altering the chromatin status of the genes. Stress treatments can cause changes in the chromatin modifications (Kim et al 2015; Lamke and Baurle 2017; Luo and He 2020). Moreover, epigenetic mechanisms play vital roles in the formation of stress memory, which may be inherited by the offspring of the stress‐treated plants (Friedrich et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2d), suggesting that the BAH-PHD-CPL2 complex acts in the same genetic pathway in flowering time control. In Arabidopsis, FLC, which is a MADS-box transcription factor that integrates multiple flowering signals, acts as a key floral repressor 31,43,44 . FLC directly represses the expression of florigen gene FT and SUPPRESSOR OF OVEREXPRESSION OF CO 1(SOC1) by binding to the promoter of SOC1 and the first intron of FT 45 .…”
Section: The Bah-phd-cpl2 Complex Represses Flowering By Inhibiting Fmentioning
confidence: 99%
“…Among them, flowering control has been a paradigmatic model for PRC complexes-mediated transcriptional repression in plants. The H3K27me3 dynamics in the flowering repressor gene FLOWERING LOCUS C (FLC) and the florigen gene FLOWERING LOCUS T (FT) play essential roles in the flowering time control 31 , and the H3K27me3 regulators influence flowering time in different ways 27,28,29,32,33,34,35,36,37,38,39,40 . Here, we demonstrated that the BAH domain-containing protein ASI1-IMMUNOPRECIPITATED PROTEIN 3 (AIPP3) and two PHD domain-containing proteins AIPP2/PARALOG OF AIPP2 (PAIPP2) could form a BAH-PHD module to read H3K27me3 and unmethylated H3K4, respectively, and coordinate in implementing transcriptional repression of hundreds of genes, particularly those development and stress-responsive genes in Arabidopsis such as the florigen gene FT and the RNA silencing effector gene AGO5.…”
Section: Introductionmentioning
confidence: 99%
“…These structural changes in chromatin are regulated by posttranslational modifications of histone, such as histone acetylation, methylation, ubiquitination, sumoylation, and phosphorylation. These modifications are accomplished by covalent modification of the N-terminal tails of core histones (Nathan et al, 2006;Sridhar et al, 2007;Luo and He, 2020). The structural change of chromatin mediated by histone acetylation is reversible and greatly influences the regulation of gene expression (Chen and Tian, 2007;Clapier and Cairns, 2009).…”
mentioning
confidence: 99%